An index of generosity for the German UI-System - Sven Schulze (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2005)
The generosity of unemployment insurance systems is constantly scrutinized by economists. Higher generosity of unemployment insurance (UI) - usually defined by referring to the replacement rate of the former wage - is commonly known to be associated with higher (equilibrium) unemployment. Unfortunately, many theoretical and empirical studies suffer from their definition of generosity. Often only pecuniary properties of the UI-system are used to capture the generosity. It can be shown however, that other characteristics of UI-systems are equally or even more important in influencing individuall behavior and in affecting overall unemployment. Most notably this refers to the time-related aspects of UI-systems as the duration of benefits, the qualification period and the waiting period. The efficiency of administering the UI-system and the stringency of monitoring and sanctions also play an important role. This paper goes beyond the usual calculation of replacement rates for the German UI-system. In order to ger a better idea of the generosity of the German UI-system from 1967 to 2003, time-related rules in German UI laws and data reflecting the administrative efficiency are incorporated into several composite measures. Contrary to conventional perception, especially when citing replacement rates alone, the resulting indices indicate that the UI-system in germany has become more generous since 1986. This increase in generosity can be identified as a factor being responsible for persistently high and rising unemployment in Germany over the last two decades.
urn:nbn:de:gbv:705-opus-16559
Keywords: C43; J65; 330; unemployment insurance; UI-generosity; index of generosity; Arbeitslosenversicherung; Lohnersatzleistungen; Dauer; Arbeitslosigkeit; Arbeitsangebot; Ökonomischer Anreiz; Deutschland